Pelayanan Screening Kesehatan Anak Usia Sekolah Di SDK Wehor Wilayah Puskesmas Haliwen Kecamatan Kakuluk Mesak - Naibili, Maria Julieta Esperanca; Rua, Yusfina Modesta; Asa, Sefrina Maria Seuk (LPPM Universitas Timor, 2023)
Schools are one of the targets of the Community-Based Total Sanitation program in the form of an area that is a strategy for improving PHBS. School-age children (6-10 years) are the most vulnerable to disease transmission. Schools can also be a place of learning and a threat of disease transmission if not appropriately managed. On the other hand, the number of school children who reach 30% of the total population of Indonesia is the potential as an